Cadmium in skelettdeformierten und normal entwickelten Kabeljau (Gadus morhua L.) in der Ostsee - Lang, Thomas; Dethlefsen, Volkert (1987)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010